Process Intensification and Optimization of Bio-Indigo Production from Indigofera tinctoria using Trichoderma Cellulase - Ismat Karim; Surachai Pornpakakul (Journal of Applied Science and Engineering, 2025)
Indigo, a natural dye traditionally extracted from plants, faces challenges in its conventional fermentation process, including low yield, poor quality, and long processing time. This study proposed an enzymatic process using Trichoderma cellulase to enhance indigo production from Indigofera tinctoria leaves powder. Indican is the main precursor for indigo production. Dried leaves powder treated with cellulase showed higher indican content compared to fresh leaves and it might not be fully released during conventional fermentation process. The indigo production with dried leaves powder by enzymatic process provided yield of 12.61mg/g which was 1.96 times higher than the fresh leaves conventional fermentation process (on dry basis). This was owing to simultaneous cellulase action for cell wall breaking to release indican and hydrolyzing indican to indigo. The purity of obtained crude indigo was also improved from 7.15% to 43.14% for conventional and enzymatic process, respectively. The optimum enzymatic process conditions were experimentally explored in triplicate and found reproducible. The enzyme stability and reusability were also improved by adding Ca^2+. This enhancement accompanied efficient use of bio-feedstock and sustainable approach to natural dye.